Effects of quercetin and menadione on intestinal calcium absorption and the underlying mechanisms - Marchionatti, Ana M. (2013)
Quercetin (QT) could be considered as a potential therapeutic agent for different diseases due to its antioxidant, anti-inflammatory, antiviral and anticancer properties. This study was designed to investigate the ability of QT to protect the chick intestine against menadione (MEN) induced injury in vivo and in vitro. Four-week old chicks (Gallus gallus) were treated i.p. with 2.5 μmol of MEN/kg b.w. or with i.l. 50 μM QT or both. QT protected the intestinal Ca2+ absorption against the inhibition caused by MEN, but QT alone did not modify. Glutathione (GSH) depletion provoked by MEN in chick enterocytes was abolished by QT treatment, whereas QT alone did not modify the intestinal GSH content. The enhancement of GSH peroxidase activity produced by MEN was blocked by QT treatment. In contrast, superoxide dismutase activity remained high after simultaneous treatment of enterocytes with MEN and QT. The flavonol also avoided changes in the mitochondrial membrane permeability (swelling) produced by MEN. The FasL/Fas/caspase-3 pathway was activated by MEN, effect that was abrogated by QT. In conclusion, QT may be useful in preventing inhibition of chick intestinal Ca2+ absorption caused by MEN or other substances that deplete GSH, by blocking the oxidative stress and the FasL/Fas/caspase-3 pathway activation.